Study on Livelihood Status of Slum Dwellers in the North Dhaka City Corporation (Journal of Environmental Science and Natural Resources, 2015)
The study was undertaken to determine the livelihood status of slum dwellers in some selected areas of North Dhaka City Corporation and to explore the relationship between livelihood statuses of slum dwellers with the selected characteristics. Data were collected from 130 slum households by using interview schedule from July to October 2012 in following a stratified random sampling procedure. Majority (43.08%) of the respondents were young in the study area. Almost one half (43.07%) of the respondents was illiterate to could sign only. Majority of the slum people were found in the low annual income category, low media contact, low training exposure and medium environmental knowledge. Overall livelihood status of the slum people was found low and majorities (65.37%) of the respondents were found having high problems (such as lack of proper waste management system, lack of proper sanitation and drainage system, water crisis than necessary and lack of proper health facilities). Relationship among the variables was determined by using the Pearsons Product Moment correlation co-efficient (r). The computed value of correlation coefficient showed that education, annual income, media contact, training exposure, and knowledge about environment showed significant positive relationship at 0.01 level of probability with their livelihood status. On the other hand, age, family size and credit had no significant relationship with their livelihood status.DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22102 J. Environ. Sci. & Natural Resources, 6(2): 89-95 2013